Absence of uncoupling protein 3 at thermoneutrality influences brown adipose tissue mitochondrial functionality in mice. Issue 11 (18th September 2020) - Silvestri, Elena; Senese, Rosalba; De Matteis, Rita; Cioffi, Federica; Moreno, Maria; Lanni, Antonia; Gentile, Alessandra; Busiello, Rosa Anna; Salzano, Anna Maria; Scaloni, Andrea; de Lange, Pieter; Goglia, Fernando; et al.
Abstract: The physiological role played by uncoupling protein 3 (UCP3) in brown adipose tissue (BAT) has not been fully elucidated so far. In the present study, we evaluated the impact of the absence of UCP3 on BAT mitochondrial functionality and morphology. To this purpose, wild type (WT) and UCP3 Knockout (KO) female mice were housed at thermoneutrality (30°C), a condition in which BAT contributes to energy homeostasis independently of its cold‐induced thermogenic function. BAT mitochondria from UCP3 KO mice presented a lower ability to oxidize the fatty acids and glycerol‐3‐phosphate, and an enhanced oxidative stress as revealed by enhanced mitochondrial electron leak, lipid hydroperoxide levels, and induction of antioxidant mitochondrial enzymatic capacity. The absence of UCP3 also influenced the mitochondrial super‐molecular protein aggregation, an important feature for fatty acid oxidation rate as well as for adequate cristae organization and mitochondrial shape. Indeed, electron microscopy revealed alterations in mitochondrial morphology in brown adipocytes from KO mice. In the whole, data here reported show that the absence of UCP3 results in a significant alteration of BAT mitochondrial physiology and morphology. These observations could also help to clarify some aspects of the association between metabolic disorders associated with low UCP3 levels, as previously reported in human studies.